(untitled) (Revista BOEM, 2024)
During the Covid-19 pandemic period, education faced multiple challenges, but also presented the opportunity to explore new forms of teaching, especially through digital resources. In this context, an educational product stemming from a master’s research, titled “Financial Literacy in School Education: digital video as a resource for Critical Mathematical Education, emerged with the purpose of offering pedagogical approaches centered on Financial Education (FE), using videos and memes as facilitating tools. Based on social, political, ethical, and environmental concerns, the conception of FE was enriched by the perspective of Critical Mathematical Education, as advocated by Ole Skovsmose. Through a virtual course on the platform Sympla.com.br, teachers and studentsshared experiences and understandings about FE, producing videos and memes.The pedagogical practices adopted explored the diverse languages of digital media, benefiting both mathematical and non-mathematical learning. The integration of digital resources,such as videos and memes, proved promising in making the teaching of Financial Education more engaging and accessible, promoting critical understanding and opportunities for skill development as outlined in the BNCC.